Polytetrahydrofuran ether amine polyurea with high elongation at break as well as preparation method and application of polytetrahydrofuran ether amine polyurea
By developing polytetrahydrofuran etheramine polyurea with high tension elongation, the micro-phase separation structure is formed using diisocyanate and polytetrahydrofuran etheramine with symmetric linear structures, which solves the problem that the existing polyurea products cannot meet the requirements of high tension elongation in high deformation areas, and achieves the high tension elongation and excellent mechanical properties of polyurea products.
Patent Information
- Application Number
- CN202411726892.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-28
AI Technical Summary
Existing polyurea products cannot meet the requirements of high-strength elongation in high deformation areas, and are difficult to meet the sealing and caulking performance of high-speed railway ball-free tracks, highways and airport runways.
A polytetrahydrofuran etheramine polyurea with high tension elongation was developed. By using diisocyanate and polytetrahydrofuran etheramine with a symmetric linear structure, and controlling the NCO/NH2 molar ratio between 1.07 and 1.00, a micro-phase separation structure composed of hard and soft segments was formed to improve the tension elongation.
The tensile elongation of polyurea products has been achieved by exceeding 1500%, meeting the sealing and caulking needs of high-deformed parts such as high-speed railways, highways and airports, and has excellent mechanical properties and a wide range of application scenarios.
Smart Images

Figure CN119591822A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymers, and in particular relates to a polytetrahydrofuran ether amine polyurea with high elongation at break, a preparation method thereof and a use thereof. Background Art
[0002] Generally speaking, "polyurethane" includes polyurethane and polyurea. From the perspective of molecular structure, polyurethane and polyurea are different. Polyurethane is a polyurethane (-NH-CO-O-) polymer, and the carbamate group is formed by the reaction of isocyanate (-N=C=O) group and hydroxyl (-OH) group. Polyurea is a polymer characterized by urea bond (-NH-CO-NR-) formed by the reaction of isocyanate (-N=C=O) group and amino (-NHR-, R is hydrogen or other substituent) group.
[0003] The one-step synthesis of polyurea is that a polyamine, a diisocyanate and a chain extender are mixed together and reacted to form a product. Linear polyurea is often prepared using a semi-prepolymer method, where an amino-terminated symmetrical linear polyetheramine is reacted with an excess of diisocyanate to form an isocyanate-terminated prepolymer and a certain amount of unreacted diisocyanate. This prepolymer mixture (containing an excess of diisocyanate) is then reacted with a diamine chain extender to form a hard segment and increase the molecular weight. Generally speaking, an increase in the hard segment content results in an increase in modulus (stiffness) and an increase in tensile strength.
[0004] At present, caulking and potting materials in specific application fields require low-temperature curing, high displacement capacity, good bonding performance, excellent durability and fatigue resistance, etc. Some single-component polyurethane adhesives generally have the problem that tensile strength and elongation at break cannot be taken into account at the same time. Under the premise of ensuring a large tensile strength, the elongation at break is often not ideal. When the higher requirements for elongation at break are met, the tensile strength is not ideal.
[0005] Patent US5,723,563 discloses a method for preparing a type of polyurethane urea (SPANDEX, also called spandex) with high elongation at break. Polypropylene oxide diol and p-diphenylmethane diisocyanate (MDI) are prepolymerized to form an isocyanate-terminated prepolymer; then, a diamine is used to extend the chain in a dimethylformamide solvent to obtain a polyurethane urea with an elongation at break of 1350%, which was the polyurethane urea with the highest elongation at break at that time. Patent CN101432326 discloses a segmented polyurethane elastomer with high elongation at break. The elastomer preparation method is: a) reacting polyether diol with isocyanate to form an OH-terminated prepolymer, b) reacting diisocyanate with the OH-terminated prepolymer to form an isocyanate-terminated prepolymer, c) converting the isocyanate-terminated prepolymer into a polyurethane elastomer using a chain extender, a suitable chain terminator and suitable other additives, and d) spinning the polyurethane elastomer into fibers, wherein less than 15% by weight of other polyurethane elastomers are present in the fibers. Tensile strength 46MPa; elongation at break 752%. Patent CN101550615 discloses a polyurethane urea elastic yarn with improved elongation and bonding strength and a preparation method thereof. The elastic yarn is a polyurethane urea prepared from polyol, two diisocyanates and a chain extender. The elastic yarn has an elongation of at least 480% and a bonding strength of at least 600mg between filaments.
[0006] Based on the above existing polyurea products, the elongation at break of polyurea products cannot reach 1500%, which is difficult to meet the requirements of sealing, caulking and other performances of high deformation parts. In view of this, for those skilled in the art, it is urgent to invent a polyurea product with high elongation at break.
[0007] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0008] The purpose of the present invention is to solve the technical problem that the polyurea products in the prior art cannot meet the requirements of high elongation at break for sealing and caulking of high deformation parts, and to provide a polytetrahydrofuran ether amine polyurea product with high elongation at break that can meet many application requirements. The polytetrahydrofuran ether amine polyurea product with high elongation at break developed by the present invention has an elongation at break of more than 1500%, and even an elongation at break of more than 2200%. The polytetrahydrofuran ether amine polyurea product of the present invention can meet the requirements of elongation at break of high elastic materials for expansion joints of high-speed railway ballastless tracks, expansion joints of highways and airport runways, and potting of electronic components. The polytetrahydrofuran ether amine polyurea product of the present invention can be applied to various fields such as automobiles, high-speed railways, construction, and aerospace, and can be used for bonding, caulking, and sealing of high deformation parts.
[0009] The first aspect of the present invention provides a polytetramethylene ether amine polyurea with high elongation at break, wherein the raw materials include: component (A) is a diisocyanate having a symmetrical linear molecular structure; component (B) is a polytetramethylene ether amine having a symmetrical linear structure, wherein:
[0010] The molar ratio of the NCO functional group of the diisocyanate having a symmetrical linear molecular structure to the NH2 functional group of the polytetrahydrofuran ether amine having a symmetrical linear structure is between 1.07 and 1.00;
[0011] The molecular structure of the polytetrahydrofuran ether amine polyurea with high tensile elongation at break is a microphase separation structure composed of hard segments and soft segments, and the weight percentage of the hard segments relative to the soft segments is greater than 20%.
[0012] When component A and component B are mixed, if component B is excessive, the molecular chain length of the polyurea material may be reduced, resulting in a polyurea material with low molecular weight and / or low mechanical properties.
[0013] The hard segments are regularly arranged in the soft segments. Crystallinity, hydrogen bonding and van der Waals interactions of the hard segments all lead to microphase separation, which affects the elongation at break. Urethane and urea bonds are desirable, both of which are chemically stable and can provide crystalline regions of the hard segments. The hard segments (crystalline domains) are immiscible with the soft segments (soft segments) (polyethers, etc.). The elongation at break of the resulting polymer is directly related to the degree of microphase separation.
[0014] Thermodynamic incompatibility causes the hard segment to be insoluble in the soft segment, resulting in microphase separation. The soft segment is usually composed of relatively long flexible polyester or polyether diols. The soft segment is non-crystalline at the temperature of use, giving the material softness and flexibility. The hard segment is usually a urethane, urea and small molecule segment. The hard segment helps to increase hydrogen bonding, resulting in higher elongation, tensile strength and hardness, but lower recovery. The hard segments are characterized by polarity because they contain urethane and urea groups, which can form intramolecular and intermolecular hydrogen bonds with ether or ester soft segments and with other urethane / urea groups; when bonded with other urethane / urea groups, they can separate themselves into structural regions rich in hard segments, and the size of the microphase separation region is In addition to the microphase separation caused by the incompatibility of hard segments and soft segments, the crystallization of the hard segments can also be the driving force for microphase separation.
[0015] In one embodiment of the present invention, the high elongation at break polytetrahydrofuran ether amine polyurea of the present invention has a higher elongation at break, and the elongation at break of the high elongation at break polytetrahydrofuran ether amine polyurea is greater than 1500%; further, the elongation at break is greater than 1800%; further, the elongation at break is greater than 2000%; further, the elongation at break is greater than 2150%; further, the elongation at break is greater than 2300%; further, the elongation at break is 2300%-2500%.
[0016] In one embodiment of the present invention, the polytetrahydrofuran ether amine having a symmetrical linear structure is obtained by esterification of polytetrahydrofuran ether diol and amino aromatic carboxylic acid. Further, the amino aromatic carboxylic acid is para-aromatic carboxylic acid and / or meta-aromatic carboxylic acid; further, the amino aromatic carboxylic acid is m-aminobenzoic acid, p-aminobenzoic acid, m-aminophenylacetic acid, p-aminophenylacetic acid, m-aminophenylpropionic acid, p-aminophenylpropionic acid, 6-amino-2-naphthoic acid.
[0017] In one embodiment of the present invention, the polytetrahydrofuran ether amine is amino-terminated polytetrahydrofuran diol diparaaminobenzoic acid ester.Amino-terminated polytetrahydrofuran diol diparaaminobenzoic acid ester has the characteristics of specific equivalent, low unsaturation and narrow molecular weight distribution (i.e. polydispersity) in the present invention.The chemical structural formula of amino-terminated polytetrahydrofuran diol diparaaminobenzoic acid ester of the present invention is as shown in formula (I):
[0018]
[0019] In the formula, R is tetramethylene, i.e. -(CH2)4-.
[0020] Further, the amino-terminated polytetrahydrofuran diol diparaaminobenzoate is selected from at least one of P1000 with an equivalent weight of 600-625, P650 with an equivalent weight of 395-415, and P250 with an equivalent weight of 220-250; further, the unsaturation of the amino-terminated polytetrahydrofuran diol diparaaminobenzoate is less than 0.007meq / g, and the molecular weight distribution of the amino-terminated polytetrahydrofuran diol diparaaminobenzoate is less than 1.30; further The unsaturation of the amino-terminated polytetrahydrofuran diol diparaaminobenzoic acid ester is less than 0.006meq / g, and the molecular weight distribution of the amino-terminated polytetrahydrofuran diol diparaaminobenzoic acid ester is less than 1.20; further, the unsaturation of the amino-terminated polytetrahydrofuran diol diparaaminobenzoic acid ester is 0.004meq / g-0.006meq / g, and the molecular weight distribution of the amino-terminated polytetrahydrofuran diol diparaaminobenzoic acid ester is 1.05-1.20. Compared with ordinary polyols or polyamines, polyols or polyamines with narrow molecular weight distribution can produce polyurethane or polyurea materials with higher elongation at break, higher strength, and wider application occasions.
[0021] In one embodiment of the present invention, the diisocyanate having a symmetrical linear molecular structure is selected from the following materials: 2,4-toluene diisocyanate (2,4-TDI), hexamethylene diisocyanate (HDI), 1,4-cyclohexyl diisocyanate (CHDI), 1,4-phenyl diisocyanate (PPDI), meta-xylylene diisocyanate (m-XDI), 2,6-toluene diisocyanate (2,6-TDI) and mixtures thereof.
[0022] Some diisocyanates such as modified 4,4'-methylene diphenyl diisocyanate (MDI), 1,5-NDI, TDI and aliphatic diisocyanate IPDI are commonly used, but they do not necessarily have a symmetrical linear structure. TDI has two isomers, 2,4-toluene diisocyanate and 2,6-toluene diisocyanate. There are several grades of commercially available TDI, pure 2,4-isomer, namely T-100; a mixture of 80% 2,4-isomer and 20% 2,6-isomer, namely T-80; a mixture of 65% 2,4-isomer and 35% 2,6-isomer, namely T-65. Using T-100 and symmetrical diols or diamines, polyurethane or polyurea with a symmetrical linear structure can be obtained. Using T-80 or T-65, polyurethane or polyurea with a symmetrical structure cannot be obtained. In pure TDI 2,4-isomer and 2,6-isomer, the two isocyanate groups are both in the meta position, and the relative positions are the same. The 2,6-form is difficult to purchase on the market and is very expensive. The 2,4-form is mass-produced and generally used. After the 2,4-form reacts with polyamines or polyols, it can form a linear macromolecule through conformational rotation.
[0023]
[0024] In one embodiment of the present invention, component (B) may also contain a symmetrical linear structure small molecule etheramine; preferably, the small molecule etheramine includes at least one of hydrogenated p-diphenylmethane diisobutylamine, 3,3'-dimethyl-4,4'-bis-sec-butylaminodicyclohexylmethane, ethylene glycol bis(3-aminopropyl) ether, diethylene glycol bis(3-aminopropyl) ether, and tetramethyl-m-xylylene diisocyanate (TMXDI).
[0025] In one embodiment of the present invention, the raw material may further include: component (C) a reactive solvent, component (D) a catalyst, and component (E) an auxiliary agent.
[0026] The reaction rate can be increased by adding a catalyst. The catalyst is selected from organic tin and amine catalysts or mixtures thereof; preferably, the catalyst is selected from stannous di(2-ethylhexanoate), stannous oleate, dibutyltin diacetate, dibutyltin dilaurate, dimethyltin dioctoate, dioctyltin dilaurate, 3-dimethylamino-N,N-dimethylpropionamide, N,N-dimethylcyclohexylamine, N,N',N',N',N'-pentamethyldiethylenetriamine, triethylenediamine and mixtures thereof;
[0027] The viscosity of the reactants can be adjusted by adding a reactive solvent, which is selected from propylene carbonate, polypropylene oxide diglycidyl ether, butanediol diglycidyl ether, hexanediol diglycidyl ether and mixtures thereof.
[0028] The auxiliary agents include 0-2wt% of a leveling agent, 0-2wt% of a defoaming agent, 0-1wt% of an anti-settling agent, 0.5-2wt% of a coupling agent, 0-1wt% of an ultraviolet light absorber, 0-1wt% of an antioxidant and 0-1wt% of a flame retardant; the colorant is selected from at least one of titanium dioxide, Sb2O3, carbon black, medium chrome yellow, phthalocyanine green and phthalocyanine blue.
[0029] The second aspect of the present invention also provides a method for preparing polytetrahydrofuran ether amine polyurea with high elongation at break, wherein the preparation method is carried out under solvent-free conditions, and the specific preparation steps include the following steps:
[0030] Step 1: Preparation of anhydrous polytetrahydrofuran etheramine of component B: Add 1 / 3-2 / 3 volume of polytetrahydrofuran etheramine with a symmetrical linear structure into a reaction container, heat to 90-100° C., evacuate to a vacuum degree of less than 0.01 MPa, heat and stir to react for 2 h-3 h, and lower the temperature to room temperature 20-40° C. under closed conditions or under nitrogen protection to obtain anhydrous polytetrahydrofuran etheramine;
[0031] Step 2: Mix the diisocyanate having a symmetrical linear molecular structure in component A and the anhydrous polytetrahydrofuran ether amine prepared in step 1 at 20-40° C., degas in vacuum, and cure for 40 seconds to 15 minutes to obtain the polytetrahydrofuran ether amine polyurea with high elongation at break.
[0032] In one embodiment of the present invention, in the step 2, after vacuum degassing, the coating is quickly coated on the object to be coated and then cured to prepare an elastic material, or quickly poured into a mold and then cured to prepare an elastic casting body.
[0033] The third aspect of the present invention also provides a use of polytetrahydrofuran ether amine polyurea with high elongation at break, wherein the polytetrahydrofuran ether amine polyurea with high elongation at break is used for sealing and caulking of high deformation areas.
[0034] Compared with the prior art, the technical effects achieved by the present invention are as follows:
[0035] (1) use the polyurea material synthesized by polytetrahydrofuran ether amine and isocyanate, the polytetrahydrofuran ether amine is preferably amino-terminated polytetrahydrofuran diol diparaaminobenzoate, which contains both ether segment and ester segment in the raw material.
[0036] (2) The raw materials of polyurea products are all linear molecules with difunctional groups, and the synthetic polyurea materials are linear polymers. Polyurea materials can also be designed as linear polymers with slight three-dimensional crosslinking, high strength and toughness. Symmetrical diisocyanates are selected. The symmetry of diisocyanates plays an important role in the performance characteristics of polyurethane. Symmetrical diisocyanates can better form dense hard segments and promote the formation of microphase separation structures. The molar ratio of the NCO functional group of the diisocyanate to the NH2 functional group of the polyamine is equal to 1.07-1.00, and polyurea with super molecular weight can be obtained.
[0037] (3) In the present invention, the terminal isocyanate reacts with the stoichiometric diamine to form a polyurea material. Since bidentate hydrogen bonds are stronger than monodentate hydrogen bonds, the urea segments produced by the polytetrahydrofuran ether amine reaction have stronger hard segments than the urethane segments produced by the diol reaction. The polyurea material has a wider operating temperature window.
[0038] (4) The polyurea material of the present invention has good toughness, high elongation at break, and elongation at break of more than 2150%. It is the polyurea material with the highest elongation at break known. It has high tensile strength, which is more than 6.3MPa, and exhibits excellent mechanical properties.
[0039] (5) In the two-component polyurea material of the present invention, both component A and component B are free of volatile solvents, and the obtained polyurea product has a solid content of 100%.
[0040] (6) The polyurea product obtained by the present invention has a wide operating temperature range, can be folded in half without breaking at 120°C, and has good mechanical properties.
[0041] (7) The polyurea production process is simple and easy to apply. It can be applied manually or by machine. It is insensitive to temperature and moisture and is less affected by ambient temperature and humidity during application.
[0042] (8) Used for bonding, caulking and sealing of high deformation parts. It is used for caulking and sealing of high-speed railway ballastless tracks, airport runways, highways, bridges and other projects. It can also be used to prepare solid tire injection materials, shock-absorbing materials, damping materials and elastomers, etc., which has great economic significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The invention discloses a process schematic diagram of a method for preparing polytetrahydrofuran ether amine polyurea with high elongation at break. DETAILED DESCRIPTION
[0044] Unless explicitly stated otherwise, throughout the specification and claims, the term “comprise” or variations such as “include” or “comprising”, etc., will be understood to include the stated elements or components but not to exclude other elements or components.
[0045] The technical solution of the present invention is described below by specific embodiments. It should be understood that one or more steps mentioned in the present invention do not exclude the existence of other methods and steps before and after the combination step, or other methods and steps can be inserted between these explicitly mentioned steps. It should also be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Unless otherwise specified, the numbering of each method step is only for the purpose of identifying each method step, and does not limit the order of arrangement of each method or limit the scope of implementation of the present invention. The change or adjustment of the relative relationship thereof can also be regarded as the scope of implementation of the present invention without substantial changes in the technical content.
[0046] The sources of the raw materials and instruments used in the examples are not particularly limited and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0047] The invention provides a two-component polytetrahydrofuran ether amine polyurea with high tensile elongation at break, wherein the raw materials include: component (A) is a diisocyanate with a symmetrical linear molecular structure; component (B) is a polytetrahydrofuran ether amine with a symmetrical linear structure, wherein the molar ratio of the NCO functional group of the diisocyanate with the symmetrical linear molecular structure to the NH2 functional group of the polytetrahydrofuran ether amine with the symmetrical linear structure is between 1.07 and 1.00; when the component A and the component B are mixed, if the component B is excessive, the molecular chain length of the polyurea material may be reduced, thereby producing a polyurea material with a low molecular weight and / or low mechanical properties.
[0048] The molecular structure of the polytetrahydrofuran ether amine polyurea with high tensile elongation at break is a microphase separation structure composed of hard segments and soft segments, and the weight percentage of the hard segments relative to the soft segments is greater than 20%.
[0049] Component (A) diisocyanate with a symmetrical linear molecular structure is selected from 2,4-toluene diisocyanate (2,4-TDI), hexamethylene diisocyanate (HDI), 1,4-cyclohexyl diisocyanate (CHDI), 1,4-phenyl diisocyanate (PPDI), meta-xylylene diisocyanate (m-XDI), 2,6-toluene diisocyanate (2,6-TDI) and mixtures thereof.
[0050] Component (B) is a polytetrahydrofuran ether amine with a symmetrical linear structure obtained by esterification of polytetrahydrofuran ether diol and amino aromatic carboxylic acid, wherein the unsaturation of the polytetrahydrofuran ether amine is less than 0.007 meq / g, and the molecular weight distribution (i.e., polydispersity) of the polytetrahydrofuran ether amine is less than 1.30. Compared with ordinary polyols or polyamines, polyols or polyamines with narrow molecular weight distribution can produce polyurethane or polyurea materials with higher elongation at break, higher strength, and wider application occasions. Molecular weight distribution is the ratio of weight average molecular weight to number average molecular weight. It is measured by gel permeation chromatography (GPC). The amino aromatic carboxylic acid is selected from para-aromatic carboxylic acid and / or meta-aromatic carboxylic acid. Specifically, the amino aromatic carboxylic acid is m-aminobenzoic acid, p-aminobenzoic acid, m-aminophenylacetic acid, p-aminophenylacetic acid, m-aminophenylpropionic acid, p-aminophenylpropionic acid and / or 6-amino-2-naphthoic acid.
[0051] More specifically, the polytetrahydrofuran ether amine is amino-terminated polytetrahydrofuran diol diparaaminobenzoic acid ester.Amino-terminated polytetrahydrofuran diol diparaaminobenzoic acid ester has the characteristics of specific equivalent, low unsaturation and narrow molecular weight distribution (i.e. polydispersity) among the present invention.The chemical structural formula of amino-terminated polytetrahydrofuran diol diparaaminobenzoic acid ester of the present invention is as shown in formula (I):
[0052]
[0053] In the formula, R is tetramethylene, i.e. -(CH2)4-.
[0054] The amino-terminated polytetrahydrofuran diol diparaaminobenzoate is selected from P1000 (equivalent weight 600-625, average weight 613), P650 (equivalent weight 395-415, average weight 405), and P250 (equivalent weight 220-250, average weight 213).
[0055] The hard segments are regularly arranged in the soft segments. Crystallinity, hydrogen bonding and van der Waals interactions of the hard segments all lead to microphase separation, which affects the elongation at break. Urethane and urea bonds are desirable, both of which are chemically stable and can provide crystalline regions of the hard segments. The hard segments (crystalline domains) are immiscible with the soft segments (polyethers, etc.). The elongation at break of the resulting polymer is directly related to the degree of microphase separation.
[0056] Thermodynamic incompatibility causes the hard segment to be insoluble in the soft segment, resulting in microphase separation. The soft segment is usually composed of relatively long flexible polyester or polyether diols. The soft segment is non-crystalline at the temperature of use, giving the material softness and flexibility. The hard segment is usually a urethane, urea and small molecule segment. The hard segment helps to increase hydrogen bonding, resulting in higher elongation, tensile strength and hardness, but lower recovery. The hard segments are characterized by polarity because they contain urethane and urea groups, which can form intramolecular and intermolecular hydrogen bonds with ether or ester soft segments and with other urethane / urea groups; when bonded with other urethane / urea groups, they can separate themselves into structural regions rich in hard segments, and the size of the microphase separation region is In addition to the microphase separation caused by the incompatibility of hard segments and soft segments, the crystallization of the hard segments can also be the driving force for microphase separation.
[0057] The polyurethane or polyurea hard segments separate into isolated microdomains that are randomly dispersed in the continuous matrix of the soft segment phase. As the hard segment content increases, the long-range interaction of the hard segments is also expected to increase, which in turn promotes the interaction of the hard segments through the soft segments. The hard segment regions act as physical crosslinking sites and strengthen the soft segments, allowing the polyurea or polyurethane to display controllable structural properties within its range of use. In addition to the hard segment content, the degree of interaction of the hard segments and the potential crystallization ability of the hard segments also have a great influence on the mechanical and thermal properties of the material. In polyurea materials, the ability of the hard segments to establish a hydrogen bond network further enhances the cohesion of the hard segments, especially within the hard segment phase.
[0058] The polyurea soft segment polyether unit has a glass transition temperature (Tg) far below room temperature. The hard segment of the polyurea material is urea-based, increasing the length of the hard segment and thus increasing the mass of the hard segment. Usually the chemical incompatibility between the soft segment and the hard segment increases with the increase in the length of the soft segment. This incompatibility drives the microphase separation process, and the soft segment Tg and the high temperature softening point of the hard segment determine the operating temperature range. The operating temperature range is usually above the soft segment Tg and below the softening point or degradation temperature of the hard segment.
[0059] A hydrogen bond is an attractive force between the lone pair of electrons of an electronegative atom (such as N or O) and a hydrogen atom directly attached to the N or O. A hydrogen bond between an electronegative O atom and a single H attached to N is called a monodentate hydrogen bond. A hydrogen bond between an electronegative O atom and H atoms attached to two different N atoms is called a bidentate hydrogen bond. The strength of hydrogen bonds in a polyurethane or polyurea chain directly affects the final properties of these materials. The hydrogen bonds in a urethane bond are monodentate, while the hydrogen bonds in a polyurea bond are bidentate. The hydrogen bond strength of polyurethane is weaker than that of polyurea. Polyetheramines and diisocyanates react directly to form polyureas, and the urea group has a greater hydrogen bond strength, which improves the physical properties of the material.
[0060] The invention provides a method for dehydrating a polytetrahydrofuran etheramine component: nitrogen is passed through a reactor, and the polytetrahydrofuran etheramine component is heated by vacuum to remove moisture and avoid side reactions caused by water. After the polyetheramine component is cooled to room temperature, a diisocyanate component and the dehydrated polyetheramine component are quickly stirred. The molar ratio of the NCO functional group of the diisocyanate to the NH2 functional group of the polyetheramine is preferably between 1.07 and 1.00.
[0061] The present invention also provides a method for preparing a polytetrahydrofuran ether amine polyurea with high elongation at break, as shown in the attached specification. Figure 1 As shown, the preparation method is carried out under solvent-free conditions, and the specific preparation steps include the following steps:
[0062] Step 1: Preparation of anhydrous polytetrahydrofuran etheramine of component B: Add 1 / 3-2 / 3 volume of polytetrahydrofuran etheramine with a symmetrical linear structure into a reaction container, heat to 90-100° C., evacuate to a vacuum degree of less than 0.01 MPa, heat and stir to react for 2 h-3 h, and lower the temperature to room temperature 20-40° C. under closed conditions or under nitrogen protection to obtain anhydrous polytetrahydrofuran etheramine;
[0063] Step 2: Mix the diisocyanate having a symmetrical linear molecular structure in component A and the anhydrous polytetrahydrofuran ether amine prepared in step 1 at 20-40° C., degas in vacuum, and cure for 40 seconds to 15 minutes to obtain the polytetrahydrofuran ether amine polyurea with high elongation at break.
[0064] The temperature for mixing two components should not be too high or too low. If the temperature is too low, the mixing will be uneven; if the temperature is too high, the reaction will be too fast and the operation period will be too short.
[0065] In a specific embodiment of the present invention, in the step 2, after vacuum degassing, the coating is quickly coated on the object to be coated and then cured to prepare an elastic material, or quickly poured into a mold and then cured to prepare an elastic casting body.
[0066] The method for the plug and socket pressure sealing test of polytetrahydrofuran ether amine polyurea is as follows:
[0067] Plug socket structure: The metal pins of the plug socket are inserted into the phenolic glass fiber reinforced plastic round plate. The round plate and the inner wall of the plug socket shell are tightly matched. After the phenolic glass fiber reinforced plastic plate with the pins is assembled, a layer of polytetrahydrofuran ether amine polyurea about 4mm thick is poured. Technical requirements: The sealed plug socket is subjected to 10 rounds of temperature cycles from low temperature -50℃ to high temperature 120℃, 2h at each temperature point, and then leak detection at room temperature 2MPa. One end of the plug socket is sealed and pressurized with argon gas, and the other end is placed in water. No bubbles are generated for 10 minutes.
[0068] Sealing design considerations: a. Primer. The metal shell of the plug socket is coated with epoxy primer to eliminate the influence of water and pollutants. b. Toughness. If the injection material is hard and brittle, it will not pass the temperature cycle test and will crack after the temperature cycle. Select polytetrahydrofuran ether amine polyurea material with high tensile elongation and good toughness. c. Strength. The plug socket needs to be leak-proof under a pressure of 2MPa. The strength of the injection material is too low to withstand the pressure requirement, so it must be both tough and pressure-resistant. d. Material selection. The polytetrahydrofuran ether amine polyurea material of Example 1.
[0069] Sealing process: a. Surface treatment of the plug socket: Aluminum and steel shells (the shell contains two kinds of metal materials) are coated with epoxy primer and cured. b. The sealing material polytetrahydrofuran ether amine component is heated and vacuumed for water-free treatment. c. All tools are dehydrated. d. The plug socket is preheated at 80℃ to achieve thermal equilibrium and remove bubbles adsorbed by metal. e. Two-component mixing temperature: 40±5℃. Mix according to proportion, vacuumize and remove bubbles. Seal. Seal multiple times, about 1-2mm each time, to eliminate thermal stress. f. Curing. Performance test.
[0070] Example 1
[0071] Preparation of anhydrous polytetrahydrofuran ether amine component B: The reaction vessel is equipped with a thermometer and an agitator, the agitator speed is 1-200 rpm, the reaction vessel is equipped with a heating interlayer, the interlayer has a heating tube and heat transfer oil, and the temperature is controllable from room temperature to 150°C. 1 / 3-2 / 3 volume of P650 (polytetrahydrofuran ether amine, Suzhou Xiangyuan New Materials Co., Ltd., equivalent N=405) is added to the reaction vessel, the temperature is raised to 90-100°C, vacuumed, the vacuum degree is less than 0.01MPa, heated and stirred for 2h-3h to obtain anhydrous P650. Subsequently, the temperature is lowered to room temperature 20-40°C under closed conditions or under nitrogen protection.
[0072] Component A uses 2,4-TDI, which can be used directly.
[0073] The temperature of component A and component B are controlled at 20-40°C, and P650 and 2,4-TDI are weighed at 405 and 87 parts by weight, respectively, and placed in an iron or plastic container. A stirrer at 100-1000 rpm is used to quickly stir and mix the mixture evenly. After vacuum degassing (in a vacuum drying oven or other vacuum equipment), the mixture is quickly coated on the object to be coated to prepare an elastic material, or poured into a mold to prepare a casting body. 100g of the mixture of components A and B is cured for 10-15 minutes.
[0074] Feilong's CPU20F-HG1 adjustable ratio pouring equipment can be used for pouring according to the above method.
[0075] Curing at 100℃ for 3h or at room temperature not lower than 30℃ for 7 days. Performance test is carried out after 7 days. The test results are shown in Table 1.
[0076] The measured tensile strength of the polytetrahydrofuran ether amine urea material is 8.5-9.2MPa, the elongation at break is 2180%-2320%, it is unbroken when folded in half at 120°C, has good thermal stability and toughness, and does not crack when immersed in liquid nitrogen temperature.
[0077] The polytetrahydrofuran ether amine polyurea obtained in Example 1 can pass the plug socket pressure sealing test.
[0078] Example 2
[0079] Preparation of anhydrous polytetrahydrofuran ether amine component B: The reaction vessel is equipped with a thermometer and an agitator, the agitator speed is 1-200 rpm, the reaction vessel is equipped with a heating interlayer, the interlayer has a heating tube and heat transfer oil, and the temperature is controllable from room temperature to 150°C. 1 / 3-2 / 3 volume of P1000 (polytetrahydrofuran ether amine, Suzhou Xiangyuan New Materials Co., Ltd., equivalent N = 613) 613.0 weight parts and tetramethyl meta-xylylene diisocyanate (TMXDI) (Yantai Wanhua, N = 122) 50.0 weight parts, 0.5 weight parts of dibutyltin dilaurate are added to the reaction vessel, the temperature is raised to 90-100°C, vacuumed, the vacuum degree is less than 0.01MPa, heated and stirred for 2h-3h to obtain anhydrous component B. Subsequently, the temperature is lowered to room temperature 20-40°C under closed conditions or under nitrogen protection.
[0080] Component A uses HDI, which can be used directly.
[0081] The catalyst used was dibutyltin dilaurate.
[0082] The temperature of the two components is controlled at 20-40°C, and they are weighed according to the weight ratio of A:B=194.5:663.5. They are placed in an iron or plastic container and quickly stirred and mixed with a stirrer at 100-1000 rpm. After vacuum degassing (in a vacuum drying oven or other vacuum equipment), they are quickly coated on the coated object to prepare an elastic material, or poured into a mold to prepare a casting body. 100g of the mixture of components A and B is cured for 10-15 minutes.
[0083] You can use Feilong's CPU20F-HG1 adjustable ratio pouring equipment to pour according to the above method, and cure at 100℃ for 3h or at room temperature not lower than 30℃ for 7 days. Perform performance test after 7 days. The test results are shown in Table 1.
[0084] The measured tensile strength of the polyurea material is 8.9-9.8MPa, and the elongation at break is 2210%-2350%. The polytetrahydrofuran ether amine polyurea material is unbroken when folded at 100°C, has good thermal stability and toughness, and does not crack when soaked in liquid nitrogen temperature.
[0085] The polytetrahydrofuran ether amine polyurea obtained in Example 2 can pass the plug socket pressure sealing test.
[0086] Example 3
[0087] 100g of polytetrahydrofuran ether amine B component P650 (polytetrahydrofuran ether amine, Suzhou Xiangyuan New Materials Co., Ltd., equivalent N=405) containing a small amount of water is placed in a plastic or glass beaker and heated in a vacuum drying oven at 100°C and a vacuum degree of less than 0.01MPa for 2h. The weight of the polytetrahydrofuran ether amine component before and after heating and vacuuming is weighed with an analytical balance to calculate the weight percentage of water. In this embodiment, the polytetrahydrofuran ether amine component P650 contains 0.2% (w) of water.
[0088] Component A uses 2,4-TDI, which can be used directly.
[0089] The temperature of the two components is controlled at 20-40°C, and the weight ratio of P650:2,4-TDI=405:90.9 is weighed, placed in an iron container, and quickly stirred and mixed with a stirrer at 100-1000 rpm. After vacuum degassing (in a vacuum drying oven or other vacuum equipment), it is quickly coated on a polyethylene flat plate to prepare an elastic material, or poured into a mold to prepare a casting body. 100g of the mixture of components A and B is cured for 10-15 minutes.
[0090] Feilong's CPU20F-HG1 adjustable ratio pouring equipment can be used for pouring according to the above method.
[0091] Curing at 100℃ for 3h or at room temperature not lower than 30℃ for 7 days. Performance test is carried out after 7 days. The test results are shown in Table 1.
[0092] The obtained polyurea material has a small amount of uniform bubbles.
[0093] The measured tensile strength of the polyurea material is 6.8-7.5MPa, and the elongation at break is 2070%-2180%. The polytetrahydrofuran ether amine polyurea material is unbroken when folded at 120°C, has good thermal stability and toughness, and does not crack when soaked in liquid nitrogen temperature.
[0094] The polytetrahydrofuran ether amine polyurea obtained in Example 3 can pass the plug socket pressure sealing test.
[0095] Example 4
[0096] Preparation of component B of polytetrahydrofuran ether amine: 100 parts by weight of polytetrahydrofuran ether amine (Suzhou Xiangyuan New Materials Co., Ltd., equivalent N=405; water content 0.2% by weight), 0.50 parts by weight of leveling agent (modified polysiloxane leveling agent, Levaslip 432, Elementis, UK), 0.50 parts by weight of defoamer (defoamer composed of defoaming polymer and polysiloxane solution, BYK-060N, BYK, Germany), 0.50 parts by weight of anti-settling agent (modified urea solution, BYK-D410, BYK, Germany), 0.50 parts by weight of coupling agent (γ-glycidyloxypropyltrimethoxysilane coupling agent, GF80, Wacker Chemical Company, Germany), 0.26 parts by weight of ultraviolet light absorber (2-(5-chloro-2H-benzotriazolyl-2)-6-(4-(2-(5-chloro-2H-benzotriazolyl-2)-6-(4-(2-(5-chloro-2H-benzotriazolyl-2)-6-(4-(2-(5-chloro-2H-benzotriazolyl-2)-6-(4-(2-(5-chloro-2H-benzotriazolyl-2)-6-(4-(2- -tert-butyltetramethylphenol, 3326, Clariant, Germany), 0.10 parts by weight of antioxidant (triethylene glycol bis-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)] propionate, 245, BASF, Germany), 0.50 parts by weight of flame retardant (dimethyl methylphosphonate, Qingdao Lianmei Chemical Co., Ltd.), 5.5 parts by weight of white Sb2O3 pigment, mix well, stir in a high-speed mixer (1000 rpm) for 1 hour, put into a sand mill and grind to a fineness of less than 50 μm, and store the discharged material in a sealed container.
[0097] Component A consists of 2,4-TDI and is used directly.
[0098] 2. The temperature of the components is controlled at 20-40°C, and the B:A components are weighed at a weight ratio of 439:87. The components are placed in an iron or plastic container and quickly stirred and mixed with a stirrer at 100-1000 rpm. After vacuum degassing (in a vacuum drying oven or other vacuum equipment), the components are quickly coated on the coated object to prepare an elastic material, or poured into a mold to prepare a casting body. 100g of the mixture of components A and B is cured for 10-15 minutes.
[0099] Feilong's CPU20F-HG1 adjustable ratio pouring equipment can be used for pouring according to the above method.
[0100] Curing at 100℃ for 3h or at room temperature not lower than 30℃ for 7 days. Performance test is carried out after 7 days. The test results are shown in Table 1.
[0101] The polyurea material produced is free of bubbles.
[0102] The measured tensile strength of the polyurea material is 7.5-8.8MPa, and the elongation at break is 2250%-2420%. The polytetrahydrofuran ether amine polyurea material is unbroken when folded at 120°C, has good thermal stability and toughness, and does not crack when soaked in liquid nitrogen temperature.
[0103] The polytetrahydrofuran ether amine polyurea obtained in Example 4 can pass the plug socket pressure sealing test.
[0104] Example 5
[0105] Preparation of anhydrous polytetrahydrofuran ether amine component B: The reaction vessel is equipped with a thermometer and an agitator, the agitator speed is 1-200 rpm, the reaction vessel is equipped with a heating interlayer, the interlayer has a heating pipe and heat transfer oil, and the temperature is controllable from room temperature to 150°C. 1 / 3-2 / 3 volume of P250 (polytetrahydrofuran ether amine, Suzhou Xiangyuan New Materials Co., Ltd., equivalent N=235) 272 parts by weight are added to the reaction vessel, the temperature is raised to 90-100°C, vacuumed, the vacuum degree is less than 0.01MPa, heated and stirred for 2-3h to obtain anhydrous P250. Subsequently, the temperature is lowered to 80-85°C under closed conditions or under nitrogen protection.
[0106] Component A consists of 2,4-TDI and is used directly.
[0107] Components A and B are 80-85°C. Weigh them according to the weight ratio of P250:2,4-TDI:propylene carbonate = 272 (85°C):101:16, put them in an iron or plastic container, use a 100-1000 rpm stirrer to quickly stir and mix them evenly, (in a vacuum drying oven or other vacuum equipment) vacuum degassing, quickly apply them on the coated object to prepare an elastic material, or pour them into a mold to prepare a casting body, 100g of the mixture of components A and B is cured for 10-15 minutes.
[0108] You can use Feilong CPU20F-HG1 adjustable ratio pouring equipment to pour according to the above method. P250 and propylene carbonate components are first mixed evenly and heated to 80-85℃.
[0109] Curing at 100℃ for 3h or at room temperature not lower than 30℃ for 7 days. Performance test is carried out after 7 days. The test results are shown in Table 1.
[0110] The measured tensile strength of the polyurea material is 6.3-7.5MPa, and the elongation at break is 2100%-2320%. The polytetrahydrofuran ether amine polyurea material is unbroken when folded at 120°C, has good thermal stability and toughness, and does not crack when soaked in liquid nitrogen temperature.
[0111] The polytetrahydrofuran ether amine polyurea obtained in Example 5 can pass the plug socket pressure sealing test.
[0112] Comparative Example 1
[0113] Preparation of anhydrous polytetrahydrofuran ether amine component B: The reaction vessel is equipped with a thermometer and an agitator, the agitator speed is 1-200 rpm, the reaction vessel is equipped with a heating interlayer, the interlayer has a heating tube and heat transfer oil, and the temperature is controllable from room temperature to 150°C. 1 / 3-2 / 3 volume of P650 (polytetrahydrofuran ether amine, Suzhou Xiangyuan New Materials Co., Ltd., equivalent N=405) is added to the reaction vessel, the temperature is raised to 90-100°C, vacuumed, the vacuum degree is less than 0.01MPa, heated and stirred for 2h-3h to obtain anhydrous P650. Subsequently, the temperature is lowered to room temperature 20-40°C under closed conditions or under nitrogen protection.
[0114] Component A is modified liquefied MDI and is used directly.
[0115] 2. The temperature of the components is controlled at 20-40°C. P650 and modified liquefied MDI are weighed at 405 and 125 parts by weight, placed in an iron or plastic container, and quickly stirred and mixed with a stirrer at 100-1000 rpm. After vacuum degassing (in a vacuum drying oven or other vacuum equipment), the mixture is quickly coated on the coated object to prepare an elastic material, or poured into a mold to prepare a casting body. 100g of the mixture of components A and B is cured for 30-40 minutes.
[0116] Feilong's CPU20F-HG1 adjustable ratio pouring equipment can be used for pouring according to the above method.
[0117] Curing at 100℃ for 3h or at room temperature not lower than 30℃ for 7 days. Performance test is carried out after 7 days. The test results are shown in Table 1.
[0118] The measured tensile strength of the polyurea material is 11.0MPa and the elongation at break is 175%. The polytetrahydrofuran ether amine polyurea material is unbroken when folded at 120°C, has good thermal stability and toughness, and does not crack when immersed in liquid nitrogen.
[0119] The polytetrahydrofuran ether amine polyurea obtained in Comparative Example 1 cannot pass the plug socket pressure sealing test.
[0120] The asymmetric structure leads to a significant decrease in the elongation at break.
[0121] Table 1 Performance comparison of polyurea materials obtained in Examples and Comparative Examples
[0122]
[0123] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made in accordance with the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is defined by the claims and their equivalents.
Claims
1. A polytetrahydrofuran ether amine polyurea with high elongation at break, characterized in that: The raw materials include: component (A) is a diisocyanate with a symmetrical linear molecular structure; component (B) is a polytetrahydrofuran ether amine with a symmetrical linear structure, wherein: The molar ratio of the NCO functional group of the diisocyanate having a symmetrical linear molecular structure to the NH2 functional group of the polytetrahydrofuran ether amine having a symmetrical linear structure is between 1.07 and 1.00; The molecular structure of the polytetrahydrofuran ether amine polyurea with high tensile elongation at break is a microphase separation structure composed of hard segments and soft segments, and the weight percentage of the hard segments relative to the soft segments is greater than 20%.
2. The polytetrahydrofuran ether amine polyurea with high elongation at break according to claim 1, characterized in that: The high elongation at break polytetramethylene ether amine polyurea has an elongation at break greater than 1500%; preferably, the elongation at break is greater than 1800%; more preferably, the elongation at break is greater than 2000%; more preferably, the elongation at break is greater than 2150%; more preferably, the elongation at break is greater than 2300%; more preferably, the elongation at break is 2300%-2500%.
3. The polytetrahydrofuran ether amine polyurea with high elongation at break according to claim 1, characterized in that: The polytetrahydrofuran ether amine having a symmetrical linear structure is obtained by esterification reaction of polytetrahydrofuran ether diol and amino aromatic carboxylic acid; preferably, the amino aromatic carboxylic acid is para-aromatic carboxylic acid and / or meta-aromatic carboxylic acid; more preferably, the amino aromatic carboxylic acid is m-aminobenzoic acid, p-aminobenzoic acid, m-aminophenylacetic acid, p-aminophenylacetic acid, m-aminophenylpropionic acid, p-aminophenylpropionic acid, 6-amino-2-naphthoic acid.
4. The polytetrahydrofuran ether amine polyurea with high elongation at break according to claim 3, characterized in that: The polytetrahydrofuran ether amine is amino-terminated polytetrahydrofuran diol diparaaminobenzoate; preferably, the amino-terminated polytetrahydrofuran diol diparaaminobenzoate is selected from at least one of P1000 with an equivalent weight of 600-625, P650 with an equivalent weight of 395-415, and P250 with an equivalent weight of 220-250; more preferably, the unsaturation of the amino-terminated polytetrahydrofuran diol diparaaminobenzoate is less than 0.007meq / g, and the decomposition of the amino-terminated polytetrahydrofuran diol diparaaminobenzoate is less than 0.010meq / g. The molecular weight distribution of the amino-terminated polytetrahydrofuran diol diparaaminobenzoate is less than 1.30; more preferably, the unsaturation of the amino-terminated polytetrahydrofuran diol diparaaminobenzoate is less than 0.006meq / g, and the molecular weight distribution of the amino-terminated polytetrahydrofuran diol diparaaminobenzoate is less than 1.20; more preferably, the unsaturation of the amino-terminated polytetrahydrofuran diol diparaaminobenzoate is 0.004meq / g-0.006meq / g, and the molecular weight distribution of the amino-terminated polytetrahydrofuran diol diparaaminobenzoate is 1.05-1.
20.
5. The polytetrahydrofuran ether amine polyurea with high elongation at break according to claim 1, characterized in that: The diisocyanate with a symmetrical linear molecular structure is selected from the following materials: 2,4-toluene diisocyanate (2,4-TDI), hexamethylene diisocyanate (HDI), 1,4-cyclohexyl diisocyanate (CHDI), 1,4-phenyl diisocyanate (PPDI), meta-xylylene diisocyanate (m-XDI), 2,6-toluene diisocyanate (2,6-TDI) and mixtures thereof.
6. The polytetrahydrofuran ether amine polyurea with high elongation at break according to claim 1, characterized in that: Component (B) may also contain a symmetrical linear structure small molecule etheramine; preferably, the small molecule etheramine includes at least one of hydrogenated p-diphenylmethane diisobutylamine, 3,3'-dimethyl-4,4'-bis-sec-butylaminodicyclohexylmethane, ethylene glycol bis(3-aminopropyl) ether, diethylene glycol bis(3-aminopropyl) ether, and tetramethyl-m-xylylene diisocyanate (TMXDI).
7. The polytetrahydrofuran ether amine polyurea with high elongation at break according to claim 1, characterized in that: The raw materials may further include: component (C) a reactive solvent, component (D) a catalyst, and component (E) an auxiliary agent; Wherein, the catalyst is selected from organic tin and amine catalysts or mixtures thereof; preferably, the catalyst is selected from stannous (2-ethylhexanoate), stannous oleate, dibutyltin diacetate, dibutyltin dilaurate, dimethyltin dioctoate, dioctyltin dilaurate, 3-dimethylamino-N,N-dimethylpropionamide, N,N-dimethylcyclohexylamine, N,N',N',N',N'-pentamethyldiethylenetriamine, triethylenediamine and mixtures thereof; The reactive solvent is selected from the group consisting of propylene carbonate, polypropylene oxide diglycidyl ether, butanediol diglycidyl ether, hexanediol diglycidyl ether, and mixtures thereof.
8. The method for preparing a polytetrahydrofuran ether amine polyurea with high elongation at break according to claim 1, characterized in that: The preparation method is carried out under solvent-free conditions, and the specific preparation steps include the following steps: Step 1: Preparation of anhydrous polytetrahydrofuran etheramine of component B: Add 1 / 3-2 / 3 volume of polytetrahydrofuran etheramine with a symmetrical linear structure into a reaction container, heat to 90-100° C., evacuate to a vacuum degree of less than 0.01 MPa, heat and stir to react for 2 h-3 h, and lower the temperature to room temperature 20-40° C. under closed conditions or under nitrogen protection to obtain anhydrous polytetrahydrofuran etheramine; Step 2: Mix the diisocyanate having a symmetrical linear molecular structure in component A and the anhydrous polytetrahydrofuran ether amine prepared in step 1 at 20-40° C., degas in vacuum, and cure for 40 seconds to 15 minutes to obtain the polytetrahydrofuran ether amine polyurea with high elongation at break.
9. The method for preparing a polytetrahydrofuran ether amine polyurea with high elongation at break according to claim 8, characterized in that: In the step 2, after vacuum degassing, the coating is quickly coated on the object to be coated and then cured to prepare an elastic material, or quickly poured into a mold and then cured to prepare an elastic casting body.
10. Use of the polytetrahydrofuran ether amine polyurea with high elongation at break according to claim 1, wherein the polytetrahydrofuran ether amine polyurea with high elongation at break is used for sealing and caulking of high deformation areas.
Citation Information
Patent Citations
Novel preparation method for polyether amine composite material
CN102161822A
Polycarbonate polyols, polyisocyanate prepolymers and polyurethane and polyurethane urea elastomers based thereon
CN111479844A
Single-component waterborne polyurethane waterproof coating and preparation method thereof
CN114181605A
Polyurethane material with dynamic performance and damping performance and preparation method thereof
CN114560991A
Highly branched polyurea material as well as preparation method and application thereof
CN115873197A
Cited By
Polyester polyol, polyurethane resin and preparation method and application thereof
CN122302242A
Degradable polylactic acid 3D printing material as well as preparation method and application thereof
CN122381536A